From Possibility to Necessity: Modality as a Rhetorical Weapon in the 2024 U.S. Presidential Debate - Reli Handayani; Ratu Khansa Arena; Ahmad Ahmad Ridha (STIT Buntet Pesantren Cirebon, 2026)
As a part from being political events, the Presidential debates can also be considered linguistics performances. Depending on how the candidates opt to convey certainty, obligation, and prediction in their claims, the audience learns more about the leadership image they are trying to project. The current paper seeks to explore the question by investigating type and function of modality in the debates of Donald Trump and Kamala Harris held within the 2024 U.S. Presidential Debate. While previous researcch has adressed the issue of modality in politicla discourse, no existing study has applied the eight sub-type framework suggested by Palmer (2001) to a articular live presidential debate from a qualitative standpoint. It is the problem this paper is going to fill covering the types of modalities appear in the 2024 U.S presidential debate and its function in the arguments of Kamala and Trump. The data drawm from the verified debate transcript published on the ABC News website. The analysis yielded 205 modal verb instances (111 by Trump and 94 by Harris), with Epistemic Assumptive being predominant subtype (82 instances) and Epistemic Deductive occuring only in Trump's speech.